1996
DOI: 10.5551/jat1994.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vitronectins in Atherosclerotic Lesions

Abstract: Vitronectin is one of the major extracellular matrix proteins that accumulates in atherosclerotic lesions. A monoclonal antibody (EMR1a/212D) specifically stained the extracellular regions in thickened intima which colocalized well with lipid deposition. The antigenic glycoprotein with a molecular weight of 66KDa was revealed to be rabbit vitronectin. When homogenates of WHHL rabbit atheroma were subjected to immunoblot analysis using EMR1a/212D, four molecules with molecular weight 66, 56, 50 and 47KDa were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…A number of reports (25,26) indicate that vitronectin accumulates in atherosclerotic plaques and is strongly expressed after vascular injury. Immunohistological staining of B3.3G on the surface of early lesions and within the plaque, near the necrotic core, where lipids are deposited in more complex plaques, is in good agreement with previously published data (27). Immunoblot experiments have shown that B3.3G detected two bands at ϳ56 and ϳ50 kDa.…”
Section: Subtractive Filter Screening After Single Round In Vivosupporting
confidence: 78%
See 1 more Smart Citation
“…A number of reports (25,26) indicate that vitronectin accumulates in atherosclerotic plaques and is strongly expressed after vascular injury. Immunohistological staining of B3.3G on the surface of early lesions and within the plaque, near the necrotic core, where lipids are deposited in more complex plaques, is in good agreement with previously published data (27). Immunoblot experiments have shown that B3.3G detected two bands at ϳ56 and ϳ50 kDa.…”
Section: Subtractive Filter Screening After Single Round In Vivosupporting
confidence: 78%
“…Immunoblot experiments have shown that B3.3G detected two bands at ϳ56 and ϳ50 kDa. Interestingly, Mori et al (27) have previously characterized the 56-and 50-kDa bands as the forms of vitronectin markedly increased in atheromatous aorta in Watanabe heritable hyperlipidemic rabbit. Taken together, these results prove that vitronectin is an attractive target for imaging atherosclerotic lesions.…”
Section: Subtractive Filter Screening After Single Round In Vivomentioning
confidence: 99%
“…On frozen sections, the following antibodies were used: LM609, a mouse monoclonal anti-human ␣ v ␤ 3 -integrin, 10 g/mL (Chemicon International Inc) 8 ; mouse anti-human osteopontin, 2.4 g/mL (University of Iowa Hybridoma Bank) 17 ; EMR 1a/212D, a monoclonal anti-rabbit vitronectin (ascites fluid, 1:4000, Dr Tatsuya Takano, Teikyo University, Japan) 18 ; RAM-11, 0.03 g/mL; Rb1/9 and Rb2/3, mouse monoclonal anti-rabbit ICAM-1 (intracellular adhesion molecule-1) and VCAM-1 (vascular cell adhesion molecule-1) antibodies (tissue culture supernatant, 1:10, Dr Myron Cybulsky, University of Toronto) 10 ; and a goat polyclonal anti-rabbit MCP-1 (monocyte chemotactic protein-1) antibody, 5 g/mL (Dr Teizo Yoshimura, National Cancer Institute, Frederick, Md). 19 A Vectastain Elite ABC kit (Vector Labs) was used to detect primary antibodies, and DAB (DAKO) was used for visualization.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…There have been many reports on sclerotic lesions of the coronary artery [7,11,13,16] and aorta [4,5,8,9] until now, but there are no reports on the arterial lesions in the influx and intravisceral arteries of the parenchymatous organs, except for the heart and brain [12], in the WHHL rabbit. In the present study, we investigated histopathologically the arteriosclerotic changes in the influx and intravisceral arteries of the liver, kidney and lung, and clarified the degree and progress level of arteriosclerosis in these parenchymatous organs.…”
mentioning
confidence: 99%